Perceptions of sustainable development of high school students in Sapiranga-RS, Brazil (Desenvolvimento em Questão, 2026)
This study aims to identify the level of understanding of sustainable development among high school students from public and private schools, analyzing how these young people position themselves in relation to the imperatives of sustainability. The research adopted a descriptive quantitative approach, using a survey applied to 239 students from public and private schools in Sapiranga/RS. The results reveal a selective adherence to sustainable practices: while there is engagement in the maintenance of electronics to combat obsolescence and in waste separation, there is resistance to collaborative economy models, such as renting and sharing goods. It was found that sociodemographic variables and the type of institution (public or private) do not exert a significant influence on the level of environmental awareness of the sample. It is concluded that, although these young people recognize the quality of ecological products, consumption behavior is still mediated by the culture of ownership. The study highlights the need for educational policies that go beyond basic recycling, fostering the collaborative economy and the second-hand market as strategies for the transition towards a circular economy.
Keywords: Sustainable Development; Conscious Consumption; Circular Economy; Sustainability; Environmental Education